Sativex® as add-on therapy vs. further optimized first-line ANTispastics (SAVANT) in resistant multiple sclerosis spasticity: a double-blind, placebo-controlled randomised clinical trial. (1st February 2019) - Markovà, Jolana; Essner, Ute; Akmaz, Bülent; Marinelli, Marcella; Trompke, Christiane; Lentschat, Arnd; Vila, Carlos
Abstract: Purpose/aim: To evaluate the efficacy of tetrahydrocannabinol (THC):cannabidiol (CBD) oromucosal spray (Sativex ® ) as add-on therapy to optimised standard antispasticity treatment in patients with moderate to severe multiple sclerosis (MS) spasticity. Methods: Sativex ® as add-on therapy vs. further optimised first-line ANTispastics (SAVANT) was a two-phase trial. In Phase A, eligible patients received add-on THC:CBD spray for 4 weeks to identify initial responders [≥20% improvement from baseline in spasticity 0–10 numerical rating scale (NRS) score]. Following washout, eligible initial responders were randomised to receive THC:CBD spray or placebo for 12 weeks (double-blinded, Phase B). Optimisation of underlying antispasticity medications was permitted in both groups across all study periods. Results: Of 191 patients who entered Phase A, 106 were randomised in Phase B to receive add-on THC:CBD spray ( n  = 53) or placebo ( n  = 53). The proportion of clinically relevant responders after 12 weeks (≥30% NRS improvement; primary efficacy endpoint) was significantly greater with THC:CBD spray than placebo (77.4 vs. 32.1%; p  < 0.0001). Compared with placebo, THC:CBD spray also significantly improved key secondary endpoints: changes in mean spasticity NRS ( p  < 0.0001), mean pain NRS ( p  = 0.0013), and mean modified Ashworth's scale ( p  = 0.0007) scores from Phase B baseline to week 12. Adverse events, when present, were mild/moderate and without new safety concerns. Conclusions: Add-on THC:CBD oromucosal spray provided better and clinically relevant improvement of resistant MS spasticity compared with adjusting first-line antispasticity medication alone.